Mechanical Stability Analysis via Neutral Mechanical Plane for High‐Performance Flexible Si Nanomembrane FDSOI Device. Issue 21 (7th September 2017) - Kim, Seung‐Yoon; Bong, Jae Hoon; Kim, Cheolgyu; Hwang, Wan Sik; Kim, Taek‐Soo; Cho, Byung Jin
Abstract: High‐performance mechanically flexible Si nanomembrane (NM) fully depleted silicon‐on‐insulator field‐effect transistors are realized via neutral mechanical plane (NMP) optimization. This NMP‐optimized Si NM flexible device, using both the analytical and numerical modeling, shows excellent mechanical and electrical stability even at a bending condition with a 1 mm radius. The strain at this point is less than 0.01% that is much smaller than the strain tolerance of 0.1%. This work reveals that mechanical reliability is heavily associated with the location of the NMP and the NMP optimization is essential to realize the Si NM flexible electronics. Abstract : High‐performance mechanically flexible Si nanomembrane (NM) fully depleted silicon‐on‐insulator (FDSOI) field‐effect transistors are realized via neutral mechanical plane (NMP) optimization. This NMP‐optimized Si NM flexible device, using both the analytical and numerical modeling, shows excellent mechanical and electrical stability even at a 1 mm bending radius. The strain at this point is less than 0.01% much smaller than the strain tolerance of 0.1%.